Efficient nanostructured 'black' silicon solar cell by copper‐catalyzed metal‐assisted etching. (13th November 2014) - Toor, Fatima; Oh, Jihun; Branz, Howard M.
Abstract: We produce low‐reflectivity nanostructured 'black' silicon (bSi) using copper (Cu) nanoparticles as the catalyst for metal‐assisted etching and demonstrate a 17.0%‐efficient Cu‐etched bSi solar cell without any vacuum‐deposited anti‐reflection coating. The concentration ratio of HF to H2 O2 in the etch solution provides control of the nanostructure morphology. The solar‐spectrum‐weighted average reflection (Rave ) for bSi is as low as 3.1% on Cu‐etched planar samples; we achieve lower reflectivity by nanostructuring of micron‐scale pyramids. Successful Cu‐based anti‐reflection etching requires a concentration ratio [HF]/[H2 O2 ] ≥ 3. Our 17.0%‐efficient Cu‐etched bSi photovoltaic cell with a pyramid‐texture has a Rave of 3% and an open circuit voltage (Voc ) of 616 mV that might be further improved by reducing near‐surface phosphorus (P) densities. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : This manuscript presents a systematic study of the concentration ratio of HF to H2 O2 in the Cu‐catalyzed 'black silicon' (bSi) etch solution that controls the nanostructure morphology. We find that Cu‐based antireflection etching requires a concentration ratio [HF]/[H2 O2 ] ≥ 3. We demonstrate a 17.0%‐efficient Cu‐etched multiscale textured bSi solar cell with a spectrum weighted average surface reflectivity of 3%, without utilizing any vacuum‐deposited anti‐reflection coating. Cu‐catalyzed bSi presents a cheap alternative to manufacture Si solar cells at industrial scale.